Activation-induced cytidine deaminase plays crucial role in ovalbumin-induced food allergy and promoted by IL-21. (October 2019) - Li, Yongning; Wang, Yongjun; Sun, Nanan; Yang, Hui; Zhang, Qiannan; Zhang, Xiaopeng; Huang, Run; Jia, Xudong
Highlights: Activation-induced cytidine deaminase (Aicda) is the highest expressed gene in the allergic mice. IL-21 can dramatically enhance the expression of Aicda in the lymph node microenvironment. IL-17A can enhance the promotion effect of IL-21 on the expression of Aicda but it has little influence by itself. The promotion effect of IL-21 on Aicda is partially through STAT3. Abstract: The prevalence of IgE-mediated food allergy is increasing in the whole wide world which often causes skin and gastrointestinal tract symptoms, or even fatal anaphylactic shock. However, the evaluation of food allergens remains difficult, and the mechanism of food allergy is still not fully clear. To study the gene expression profile in food allergy animal models and identify the regulatory mechanism of the crucial genes, two administration routes were used to build animal models in our study. OVA-specific IgE and IL-4 levels were tested by ELISA, transcriptome profiling was carried out by microarray, and the regulatory mechanism of the highest expressed gene was studied in the primary spleen cells. We found that activation-induced cytidine deaminase (Aicda) is the highest expressed gene in the allergic mice, IL-21 can dramatically enhance the expression of Aicda in the lymph node microenvironment, and IL-17A can promote this effect significantly though it has only limited influence by itself. At last, we illuminated that the promotion of IL-21 on Aicda is partially through STAT3. In summary, our results suggest that IL-21 and IL-17A may play important role in the expression of Aicda as well as food allergy.